2017
DOI: 10.1002/prep.201700171
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Elaboration of HMX and HMX Composites by the Spray Flash Evaporation Process

Abstract: The Spray Flash Evaporation (SFE) process invented and developed at the NS3E laboratory allows obtaining different nanosized explosives (TNT, RDX, CL‐20…). This process is based on the very fast evaporation of the solvent due to the drastic modification of pressure and temperature leading to the crystallization of the molecules present in solution into nanometric or submicrometric particles. Here, we show the possibility to prepare pure HMX (Octahydro‐1,3,5,7‐tetranitro‐1,3,5,7‐tetrazocine) or HMX based compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[19] Up to now, many methods have been utilized to prepare nEMs, such as sol-gel technology, mechanical grinding method, solvent/non-solvent and spraying evaporation and supercritical fluid technology, new type methods including spraying flash evaporation and so on. [20][21][22][23][24][25] Synthesis of nEMs using sol-gel chemistry is performed in solution, possessing more convenience than conventional methods in low-temperature preparation, easy to be controled over the stoichiometry and homogeneity. Therefore, various nEMs have been prepared by sol-gel technology, including (annonium perchlotate) AP/ RDX/SiO 2 , HMX-AP-SiO 2 , (Resorcinol-formaldehyde) RF/RDX, HMX/AP/RF and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Up to now, many methods have been utilized to prepare nEMs, such as sol-gel technology, mechanical grinding method, solvent/non-solvent and spraying evaporation and supercritical fluid technology, new type methods including spraying flash evaporation and so on. [20][21][22][23][24][25] Synthesis of nEMs using sol-gel chemistry is performed in solution, possessing more convenience than conventional methods in low-temperature preparation, easy to be controled over the stoichiometry and homogeneity. Therefore, various nEMs have been prepared by sol-gel technology, including (annonium perchlotate) AP/ RDX/SiO 2 , HMX-AP-SiO 2 , (Resorcinol-formaldehyde) RF/RDX, HMX/AP/RF and so on.…”
Section: Introductionmentioning
confidence: 99%
“…A further strategy to enhance energetic performances and sensitivity thresholds of secondary explosives is the formulation of composite materials. Desensitization of energetic compounds is enabled for instance by combining secondary explosives with polymers [12][13][14], with further secondary explosives [15,16], with metal oxides [17] or with graphite or nanodiamonds [18,19]. The formulation of such composites improves the mechanical stability, and decreases sensitivity against friction, impact and ESD [18].…”
Section: Introductionmentioning
confidence: 99%
“…[27] Denis Spitzer et al demonstrated the continuous preparation of pharmaceutical (Caffeine/Oxalic acid, Caffeine/Glutaric acid) and energetic (CL-20/TNT, CL-20/HMX) micro-and nano-cocrystals using the spray flash evaporation (SFE) process. [28] Vincent Pichot et al studied the elaboration of TNT, HMX, and HMX composites by the SFE process [29,30]. (2,4-DHB) nM micro-nano spheres that could catalyze the thermal decomposition of AP were successfully produced by ultrasonic spray drying technology [31].…”
Section: Introductionmentioning
confidence: 99%